Mothers - Manchevski, Milcho; Samoilovski, Vladimir; Stojanovska, Ana; Jacev, Vladimir; Gjorgjievski, Dimitar
Macedonian director Milcho Manchevski continues down his distinctive artistic path in his fourth feature, "Mothers", which is about women of all shapes and sizes, not just maternal figures. Structured in three parts like his Oscar-nominated debut "Before the Rain", it mixes fiction (the first two episodes) with documentary for an interesting result that’s more compelling than the film’s underlying philosophical questions. Manchevski says "Mothers" was inspired by the artwork of Robert Rauschenberg and is about the nature of truth, specifically our very subjective perception of truth. Perceptions of reality are stock themes for experimental filmmakers, yet despite the highbrow concept of "Mothers", the film’s three sections are relatively linear and hit home on an emotional rather than intellectual level. [www.hollywoodreporter.com]